ANALYSIS OF INDICATORS OF PACKET SERVICES OF THE NETWORK - Olimov , Olimboy Otabekovich (Educational Research in Universal Sciences, 2024)
Accurate and in-depth analysis of network performance is a complex process. Network functionality can only cover a subset of the ever-changing workloads that processes on the network experience, which can lead to unexplored node states and sub-optimal performance in live traffic. is considered Queuing theory and network calculus techniques can provide tight bounds on performance metrics, but typically require approximations of the state of network components and the traffic arrival order with short and well-executed mathematical functions. As such, they are not immediately applicable to emerging workloads and the new algorithms and protocols developed to handle them. We explore a different approach: using formal methods to analyze network performance. We show that application synthesis techniques can be used to accurately model network components and their queues and automatically generate concise interpretable workloads in response to performance metrics queries. Our approach offers a new point in the field of available tools for network performance analysis: it is more complete than simulation and emulation and can be easily applied to algorithms and protocols expressed in first-order logic. We demonstrate the effectiveness of our approach by analyzing packet scheduling algorithms and a small leaf-spine network and creating compact workloads that may suffer from throughput, fairness, starvation, and latency issues.